Mobile sedentism? The Marakwet settlements of the Elgeyo Escarpment, north-western Kenya - David K. Kay (Afriques)
Whilst mobility has long been a key theme within African archaeology, its study has usually focussed on cases of far-ranging nomadism, particularly amongst ‘hunter-gatherer’ pastoralist populations. Conversely, changes in the form and distribution of sedentary settlement have most commonly been studied across wide spatio-temporal ranges that do not consider the role of mobile livelihood practices at scales appreciable to the people who actually performed them. This paper seeks to rectify this scholarly lacuna through the practical application of the concept of ‘shifting sedentism’ amongst the communities of Kenya’s northern Elgeyo Escarpment. Combining archaeological/contemporary household survey data with local oral histories, this paper explores how the incremental movement of individual housing compounds has contributed to the gradual shift of Marakwet settlement across the landscape over the past two centuries. Shifting patterns of residence will be linked with broader trends in mobile livelihood practice that extend across the surrounding landscape and run through multiple generations. These practices have themselves adeptly incorporated many major changes to community lifeways—including the introduction of new crops, Christian missionisation, road building and the growth of small commercial centres. Such practices embody a particularly flexible approach to socio-cultural continuity, in which situational mobility has been vital in ensuring the overarching resilience of these communities and the rugged landscape they call home. Fine-grained and multi-disciplinary approaches are key to the recognition of mobility’s importance within such otherwise sedentary contexts, and it is hoped this particular study will inspire further such efforts across the continent.